2015
DOI: 10.3413/nukmed-0686-14-07
|View full text |Cite
|
Sign up to set email alerts
|

11C-methionine PET/CT after in conclusive 99mTc-MIBI-SPECT/CT for localisation of parathyroid adenomas in primary hyperparathyroidism

Abstract: PET/CT with 11C-methionine is a very sensitive method for the detection of parathyroid adenomas, even if they are too small to be visualized by 99mTc-MIBI-SPECT/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 9 publications
1
26
0
4
Order By: Relevance
“…In previous studies, 11 C-methionine has been shown to be of great value, especially, but not only, in the setting of negative 99m Tc-sestamibi results (14)(15)(16)(17). The pooled sensitivity in a metaanalysis of 9 studies with a total of 137 patients was found to be 86% (24).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In previous studies, 11 C-methionine has been shown to be of great value, especially, but not only, in the setting of negative 99m Tc-sestamibi results (14)(15)(16)(17). The pooled sensitivity in a metaanalysis of 9 studies with a total of 137 patients was found to be 86% (24).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, problems arise if neither imaging modality can locate the PTA or if the results obtained by imaging are inconclusive or discordant. 11 C-methionine PET/CT has been successfully applied in this setting (14)(15)(16)(17)(18). During the last few years, radiolabeled choline has been increasingly used to localize PTAs, with high sensitivities reported (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…After full text review, 24 papers were included. These were subdivided by radiopharmaceutical: 14 studies investigated 11C-MET, one [ 11 C]2-hydroxy- N , N , N -trimethylethanamium (11C-CH), six 18F-FDG, one 6-[ 18 F] fluoro- l -DOPA (18F-DOPA), and three N -[( 18 F)Fluoromethyl]-2-hydroxy- N , N -dimethylethanaminium (18F-FCH) [1336]. Excluded were studies that had fewer than five patients, abstracts from conferences without available full text, and redundant studies investigating the same population.…”
Section: Resultsmentioning
confidence: 99%
“…In Beggs et al, also patients in whom other imaging techniques such as MIBI scanning, CT, or ultrasound had earlier failed to localize the adenoma were selected. In a recent smaller study with 18 patients, Braeuning et al found a sensitivity per patient of 91.7% and a sensitivity per lesion of 73.3% after a prior negative 99m Tc-MIBI-SPECT/CT [ 24 ]. Another smaller study by Chun et al who included 16 patients found a sensitivity of 91.7%, but did not select patients with prior negative imaging [ 20 ].…”
Section: Discussionmentioning
confidence: 99%